Ideology of ISIS: Social and Linguistic Practices of Abu Bakkar Al Baghdadi’s First speech - Abdulhadi, Manal Ni’met (Al-Adab Journal, 2020)
To the best of the researcher’s knowledge many studies (e.g., Bunzel: 2015) have been conducted studying the social practices of ISIS discourse only. Others (e.g, Buckingham, and Alali: 2019) focus upon the linguistic aspects of that discourse. The present paper aims at filling this gap by investigating both the social and the linguistic elements that characterize ISIS ideology. The present study focuses on analyzing the first speech delivered by Abu Bakkar Al Baghdadi in 2014 through implementing critical discourse analysis methodologies. The objective of this analysis is to outline the ideology of ISIS through exploring the critical social and cultural aspects together with the linguistic features in the text under investigation. The study will adopt an eclectic model of analysis and research based on Fairclough’s (1992) principles of critical discourse analysis and Van Dijik’s ( 1980) framework of semantic structures (topics). Both global and local semantics are studied so as to relate social to linguistic practices and vise versa. The results of the research show that this speech has a distinctive tactic language that is full of figures of speech, in particular euphemism and dysphemism that help the speaker transfer his intended ideologies.